Socioeconomic Position and Health Outcomes Following Critical Illness: A Systematic Review. Issue 6 (June 2019) - Jones, Jennifer R. A.; Berney, Sue; Connolly, Bronwen; Waterland, Jamie L.; Denehy, Linda; Griffith, David M.; Puthucheary, Zudin A.
Abstract : Objectives: Systematically review evidence examining association between preadmission socioeconomic position and physical function, health-related quality of life and survival following critical illness. Data Sources: Four electronic databases (MEDLINE, Embase, CINAHL, CENTRAL) and personal libraries were searched. Reference lists of eligible articles were cross-checked. Study Selection: Primary quantitative studies reporting association between socioeconomic position and physical function, health-related quality of life, or survival of adults admitted to the ICU were included. Data Extraction: Performed by two reviewers independently in duplicate using a prepiloted data extraction form. Quality appraisal was completed by two reviewers independently in duplicate using standardized algorithms and checklists. The Preferred Reporting Items for Systematic Reviews guidelines were followed. Data Synthesis: From 1, 799 records, 10 studies were included, one examining association of socioeconomic position with health-related quality of life and five with survival. Four studies accounted for socioeconomic position in survival analyses. Patients with lower socioeconomic position were found to have higher ICU, in-hospital, 30-day, and long-term mortality and lower 6-month Short Form-12 Mental Component Summary scores. No articles examined socioeconomic position and performance-based physical function. Notable variability in methods of socioeconomic position assessment was observed. Conclusions: Lower socioeconomic position is associated with higher mortality and lower 6-month Short Form-12 Mental Component Summary scores following critical illness. Effect on performance-based physical function is unknown. We make recommendations for consistent socioeconomic position measurement in future ICU studies. Abstract : Supplemental Digital Content is available in the text.